IMPLEMENTASI KEBIJAKAN DANA DESA DI DESA NGLURUP KECAMATAN SAMPUNG KABUPATEN PONOROGO - Satwoto, Junjung Adi (JI@P, 2021)
A village is placed as a subject that will be the main goal of government organizations in achieving successful development and improving community welfare. To achieve them, the government provides budget funds for every village throughout Indonesia to carry out village development. One of them is the Village Fund policy. Village Fund are funds sourced from the State Revenue and Expenditure Budget allocated to villages that are transferred through the Regency/ City Regional Revenue and Expenditure Budget then proceed to the Village Revenue and Expenditure Budget and are used to finance governance, implementation of development, community development and empowerment. The purpose of this study is to describe the implementation of the Village Fund Policy in Nglurup Village, Sampung District, Ponorogo Regency. To find out how the implementation of the Village Fund policy in Nglurup Village, Sampung District, Ponorogo Regency, the researcher used the George C. Edward theory. In this theory, it is stated that policy implementation is influenced by four variables, namely communication, resources, disposition and bureaucratic structure. This type of research used in this research is descriptive qualitative. Data collection techniques used are interviews, observation and documentation study. The results showed several factors that had not been fulfilled optimally, including: first, from the communication side, the socialization carried out had not been maximally conveyed because it was only through village meetings which were only attended by representatives from village institutions. Second, there are still sharing roles for activities so that policy implementation is not optimal. Third, in terms of implementation there is already a division of tasks but they still carry out more than one job.